Evaluation of glyphosate and AMPA in honey by water extraction followed by ion chromatography mass spectrometry. A pilot monitoring study. Issue 16 (10th April 2019) - Pareja, Lucia; Jesús, Florencia; Heinzen, Horacio; Hernando, María Dolores; Rajski, Łukasz; Fernández-Alba, Amadeo R.
Abstract : Two straightforward methods for glyphosate and AMPA analysis in honey through ion chromatography coupled to Q-Orbitrap accurate high-resolution mass spectrometry as well as their application to real samples are presented. Abstract : Two straightforward methods for glyphosate and AMPA analysis in honey through ion chromatography coupled to Q-Orbitrap accurate high-resolution mass spectrometry as well as their application to real samples are presented. The sample preparation step is accomplished through dilution with methanol–water or water. No pH adjustment is necessary. Recoveries were in the range 80 to 110% with RSDs < 20%. The LOQ of glyphosate was 0.005 mg kg −1, far below the allowed EU-MRL (0.05 mg kg −1 ) in honey, showing a linear range of 0.005–0.5 mg kg −1 and medium matrix effect. LOQ of AMPA was 0.02 mg kg −1 . Glyphosate quantitation was performed with internal or external calibration yielding identical results, thus broadening the applicability of the method as isotopically labelled standards are no longer mandatory. The method was applied to 32 honey samples from different origins. Glyphosate was found in 81% of the samples and 41% were above the EU-MRL showing its applicability in routine work. AMPA was not detected in any of the samples.